Pharmacist-documented interventions during the dispensing process in a primary health care facility in Qatar - Hooper, Richard (Dove Medical Press, 2009)
OBJECTIVES: To characterize prescribing error interventions documented by pharmacists in four pharmacies in a primary health care service in Qatar. METHODS: The study was conducted in a primary health care service in the State of Qatar in the period from January to March 2008. Pharmacists in four clinics within the service used online, integrated health care software to document all clinical interventions made. Documented information included: patient’s age and gender, drug therapy details, the intervention’s details, its category, and its outcome. Interventions were categorized according to the Pharmaceutical Care Network Europe Classification of drug-related problems (DRP). RESULTS: The number of patients who had their prescriptions intercepted were 589 (0.71% of the total 82,800 prescriptions received). The intercepted prescriptions generated 890 DRP-related interventions (an average of 1.9% DRPs identified across the four clinics). Fifty-four percent of all interventions were classified as drug choice problems, and 42% had safety problems (dose too high, potential significant interaction). The prescriber accepted the intervention in 53% of all interventions, and the treatment was changed accordingly. Interventions as a result of transcription errors, legality and formulary issues were eliminated from this study through the use of computerized physician order entry (CPOE). CONCLUSIONS: Documenting and analyzing interventions should be a routine activity in pharmacy practice setting in primary health care services. Educational outreach visits and other strategies can improve prescribing practices and enhance patient safety.